(untitled) (Biological Sciences - PJSIR, 2007)
Study of the i nfl uence of var ious carbon sources on prod uction of vitami n 8 by Pseudomonas sp. PCSTR 99 showed that methanol, meth ylami ne and I , 2-propanediol promoted vitam i n 8 production when grown on the modi fi ed basal m ed i um emended w ith 0.2% 5, 6-dimethyl ben zi mid azole. Amon g the nitrogen sources tested , L-aspartate and L-meth ion i ne enhanced vi tami n 8 production and cell mass dramatical l y. Any upward or down 12 1 2 ward change i n pH from 6.5 and i n temperature from 32 °C decreased the l evel of vi tami n 8 i n the m ed i um. Whereas, I 0% oxygen and 0.004 mM cobalt ion concentration i ncreased vitami n 8 prod uction si gnificantl y. f t i s 12ferred th at v itamin 8 prod u ction can also be regulated by proper mani pu l ation of ph ysical parameters of the m ed i u m as wel l.